2021
DOI: 10.1002/stem.3349
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic sensor O-GlcNAcylation regulates megakaryopoiesis and thrombopoiesis through c-Myc stabilization and integrin perturbation

Abstract: Metabolic state of hematopoietic stem cells (HSCs) is an important regulator of self-renewal and lineage-specific differentiation. Posttranslational modification of proteins via O-GlcNAcylation is an ideal metabolic sensor, but how it contributes to megakaryopoiesis and thrombopoiesis remains unknown. Here, we reveal for the first time that cellular O-GlcNAcylation levels decline along the course of megakaryocyte (MK) differentiation from human-derived hematopoietic stem and progenitor cells (HSPCs). Inhibitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…During human hematopoiesis, both erythrocytes and megakaryocytes are derived from a committed progenitor, called megakaryocyte–erythroid progenitors (MEPs) [ 38 , 39 ]. We have demonstrated in our recent study that metabolic sensor O -GlcNAcylation plays an essential role in megakaryopoiesis from HSPCs and platelet production from megakaryoblasts/megakaryocytes via the regulation of c-Myc-mediated integrin-α4 and integrin-β7 [ 40 ]. In this study, we extend the knowledge on the roles of O -GlcNAcylation in erythropoiesis, starting from the lineage specification of HSPCs to terminal differentiation and erythroid maturation.…”
Section: Discussionmentioning
confidence: 99%
“…During human hematopoiesis, both erythrocytes and megakaryocytes are derived from a committed progenitor, called megakaryocyte–erythroid progenitors (MEPs) [ 38 , 39 ]. We have demonstrated in our recent study that metabolic sensor O -GlcNAcylation plays an essential role in megakaryopoiesis from HSPCs and platelet production from megakaryoblasts/megakaryocytes via the regulation of c-Myc-mediated integrin-α4 and integrin-β7 [ 40 ]. In this study, we extend the knowledge on the roles of O -GlcNAcylation in erythropoiesis, starting from the lineage specification of HSPCs to terminal differentiation and erythroid maturation.…”
Section: Discussionmentioning
confidence: 99%
“…O -GlcNAcylation, mediated by the cycling enzymes OGT and OGA, contributes to the regulation of hematopoiesis, which produces and replenishes various cell types comprising the blood system, by means of HSC fate decision and lineage specification ( Zhang et al, 2019 ; Luanpitpong et al, 2021 ; Luanpitpong et al, 2022a ; Luanpitpong et al, 2022b ). Recent studies have demonstrated that O -GlcNAcylation also affects the functions of red blood cells and various immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…The extent of O -GlcNAcylation generally reflects the global metabolic dynamics in the cells, and hence, it serves as an ideal metabolic sensor that participates in the regulation of various cellular processes through changes in protein function, gene expression, and cellular signaling. We previously reported that O -GlcNAcylation is a key determinant of human HSC fate decision and certain lineage-specific differentiation, including megakaryopoiesis ( Luanpitpong et al, 2021 ), erythropoiesis ( Luanpitpong et al, 2022a ), and dendritic cell development ( Luanpitpong et al, 2022b ). Inhibition of OGT that causes a prolonged decrease in O -GlcNAcylation promotes megakaryopoiesis and subsequent thrombopoiesis through the perturbation of cell adhesion molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Given that BMP4, SCF, and VEGF have already been supplemented in the used hematopoietic differentiation medium, we may additionally include growth factors or small molecule inhibitors that manipulate WNT/β-catenin and Activin/Nodal signaling, e.g., Activin A, CHIR99021 (GSK-3 inhibitor), and SB-431542 (TGFβ inhibitor) [ 14 ]. Moreover, we are currently investigating the roles of O -GlcNAcylation, a nutrient-sensitive posttranslational modification of proteins, in HPC differentiation from iPSCs, as we previously found that O -GlcNAcylation is a key determinant of hematopoietic stem cell (HSC) fate decision and certain lineage-specific differentiation processes, including megakaryopoiesis [ 38 ], erythropoiesis [ 39 ], and dendritic cell differentiation [ 40 ]. For improving NK commitment, we may further increase the concentrations of major cytokines, such as IL-7 and IL-15, or introduce an additional stage of lymphoid progenitor expansion before NK cell commitment.…”
Section: Discussionmentioning
confidence: 99%